Reference values for T, B and NK human lymphocyte subpopulations in adults - P.A. Apoil; B. Puissant-Lubrano; N. Congy-Jolivet; M. Peres; J. Tkaczuk; F. Roubinet; A. Blancher (Data in Brief, 2017)
The data presented in this paper are reference ranges for frequencies of thirty-eight subpopulations of T, B and NK lymphocytes, established from a cohort of 253 healthy blood donors aged from 19 to 67. When relevant, the influence of age or sex was taken into account to calculate these reference values. This article is related to the research article entitled “Influence of age, sex and HCMV-serostatus on blood lymphocyte subpopulations in healthy adults” (Apoil et al., 2017) [1]. Immunophenotyping data obtained from each individual is made publicly available for extended analyses.